Impact of Dividend Policy on Share Price Volatility: UK Evidence - ZHANG, YIDING (2012)
This research attempts to shed light on the linkage between dividend policy and share price volatility in the context of UK. As a rework and extension of pervious research, the study is expected to reveal the potential impact of dividend change on the fluctuation of stock price, taking existing theoretical and empirical framework as basis. A snapshot of UK economy is provided after the preceding introductory section. The third chapter consists of a review of theories and empirical studies. With respect to the empirical analysis, 170 firms from seven broad industries covered by the London Stock Exchange (LSE) are chosen as the research sample, within a time span of 10 years (2001-2010). A crude linear regression is applied followed by the panel data procedure to explicitly investigate the relationship between share price movement and dividend policy. Additional variables are taken into account for controlling joint effect on dividend and volatility. A disaggregation of general industry analysis is also conducted for industry-specific effect. The main findings are consistent with the theories, suggesting a significant impact of dividend policy on the volatility of share price movement. The result of aggregate data implies significant effect of variables included on the share price volatility whereas size has tiny impact on it. In particular, dividend yield and firm leverage are positively correlated with share price volatility while dividend payout ratio is on the contrary. Return on equity, firm size and asset growth likewise inversely correlate with volatility. To some extent, this paper tends to tackle the insufficiency of existing research on dividend effect on share risks in the UK. In order to achieve a more favourable movement in share prices, a trade-off between dividend payment and retained earnings should be strategically approached. Besides, the peculiarity of UK economy and the nature of investors should always be considered in making dividend decisions. Relevant research is expected to contribute to investors’ prediction of stock price movement, performance of policy makers and practitioners as well.